Fostering active choice to empower behavioral change to reduce cardiovascular risk: A web-based randomized controlled trial. - Lorraine L Landais; Judith G M Jelsma; Olga C Damman; Evert A L M Verhagen; Danielle R M Timmermans (PLoS ONE)
Objective To investigate the effect of an active choice (AC) intervention based on creating risk and choice awareness-versus a passive choice (PC) control group-on intentions and commitment to cardiovascular disease (CVD) risk-reducing behavior. Methods Adults aged 50-70 (n = 743) without CVD history participated in this web-based randomized controlled trial. The AC intervention included presentation of a hypothetical CVD risk in a heart age format, information about CVD risk and choice options, and a values clarification exercise. The PC group received a hypothetical absolute numerical CVD risk and brief information and advice about lifestyle and medication. Key outcomes were reported degree of active choice, intention strength, and commitment to adopt risk-reducing behavior. Results More AC compared to PC participants opted for lifestyle change (OR = 2.86, 95%CI:1.51;5.44), or lifestyle change and medication use (OR = 2.78, 95%CI:1.42;5.46), than 'no change'. No differences were found for intention strength. AC participants made a more active choice than PC participants (β = 0.09, 95%CI:0.01;0.16), which was sequentially mediated by cognitive risk perception and negative affect. AC participants also reported higher commitment to CVD risk-reducing behavior (β = 0.32, 95%CI:0.04;0.60), mediated by reported degree of active choice. Conclusions Fostering active choices increased intentions and commitment towards CVD risk-reducing behavior. Increased cognitive risk perception and negative affect were shown to mediate the effect of the intervention on degree of active choice, which in turn mediated the effect on commitment. Future research should determine whether fostering active choice also improves risk-reducing behaviors in individuals at increased CVD risk in real-life settings. Trial registration ClinicalTrials.gov: NCT05142280. Prospectively registered.